ROLE OF THE TOURISM OFFICE IN THE DEVELOPMENT OF THE TONDOK BAKARU TOURISM VILLAGE AREA IN MAMASA REGENCY, WEST SULAWESI PROVINCE - Baso, Frengki Tinus; Guntur, Muhammad; Ismail, Ismail (Universitas Negeri Makassar, 2025)
The problem in this research is the role of the Mamasa Regency Tourism Office and the supporting and inhibiting factors in developing the Village Area. This research aims to determine the role and factors that support and hinder the Tourism Department in developing the Tondok Bakaru Tourism Village Area in Mamasa Regency, West Sulawesi Province.Type of qualitative descriptive research. The informants in this study were 4 people. Data collection techniques consist of observation, in-depth interviews with research informants and documentation. The results of this research indicate that the role of the Mamasa Regency Tourism Office as a motivator, facilitator and dynamist is not yet optimal in increasing tourism development, considering that mentoring, monitoring award giving, procuring budgets, making regulations, and encouraging collaboration, innovation, cultural preservation, accelerating licensing, encouraging investment are not goes well.